2018
DOI: 10.1111/apa.14324
|View full text |Cite
|
Sign up to set email alerts
|

Extraintestinal manifestations were common in children with coeliac disease and were more prevalent in patients with more severe clinical and histological presentation

Abstract: EIM were common in coeliac disease and associated with more severe clinical and histological presentation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
36
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 31 publications
5
36
0
1
Order By: Relevance
“…The prevalence rates of the patients were different due to different age ranges and symptoms which were evaluated as EIM of the patients included in the study. However, some studies have reported that the prevalence of EIM in celiac patients is approximately 60% (12,13). In our study, we found the EIM prevalence in 87% of adult celiac patients.…”
Section: Discussionsupporting
confidence: 50%
See 3 more Smart Citations
“…The prevalence rates of the patients were different due to different age ranges and symptoms which were evaluated as EIM of the patients included in the study. However, some studies have reported that the prevalence of EIM in celiac patients is approximately 60% (12,13). In our study, we found the EIM prevalence in 87% of adult celiac patients.…”
Section: Discussionsupporting
confidence: 50%
“…Along with recent studies reported the prevalence of arthritis between 2-9%, in our study which arthralgia is added, joint involvement was found as 41.7% (12,13,25,26). In addition, the prevalence of oral involvement in studies is very contradictory, it has been reported in the range of 1-83% (13,26). It is thought that the different symptoms which were evaluated as oral involvement of the patients included in the study.…”
Section: Discussionsupporting
confidence: 47%
See 2 more Smart Citations
“…Meanwhile, Nurminen et al. report that extraintestinal manifestations were common in children with coeliac disease.…”
Section: Dietitian Visits Provided Safe and Cost‐effective Follow‐up mentioning
confidence: 99%